(3QhVI GdCNHGQ hcfhR GdCSQGQ hfcJ GdBKGQ hehGYX GdCNHGQ hedM GdCTYGQ hYLGFH GdCSeGQs - (3CHh eMeO jhSa Hf eMeO Hf GdMajU, GdMLhQjs
(3ChdgG (B:s
(3GdMeO ddg GdPi dG jeKd HGdGacGQ , hdGjOQc HGdCHUGQ s
(3Jedc HGSe YeQh Hf SdjeGf Hf gTje Hf YGeQ Hf CHj GdYTjQI GdeWQis
(3de jPcQ Ydjg GSe eDdas
(3hai fSNJjf HQdjf hejdGfh ef gPG GdcJGH Cf GdeDda gh GdMLhQis
(3fSNI KGfjI s
(3fSNI OGQ GdcJH GdeUQjI Cf GdeDda gh GHf GdYTjQI GdeWQi (B"(3GfXQ Qbe (B265 (3JGQjNs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs